A pathway to net zero emissions for healthcare. (1st October 2020) - Salas, Renee N; Maibach, Edward; Pencheon, David; Watts, Nick; Frumkin, Howard
Abstract : The healthcare sector has a profound responsibility and opportunity to reduce greenhouse gas emissions to limit the widespread health harms of climate change. Renee N Salas and colleagues chart a path to net zero emissions for healthcare